Integrasi Moda Transportasi Air Dalam Operasi Militer: Kajian Perbandingan Operasi Normandia Dan Tantangan Geografis Indonesia - Wibowo, Harry; Suradi; Sugiri (Jurnal Syntax Fusion, 2026)
Water transport integration is a critical prerequisite for military mobility in Indonesia as an archipelagic state; however, geographic fragmentation, uneven readiness of ports and landing points, and limited capacity of implementing units continue to constrain system-wide interoperability. This study aims to assess the current condition of water-transport integration in supporting Indonesia’s military mobilization, to identify key success factors of integration drawn from the Normandy Operation as a conceptual benchmark, and to formulate priorities for strengthening integration to improve mobilization effectiveness in an island environment. The research adopts a qualitative approach through a case study design and comparative analysis. Data were collected from interviews, field observations, and a review of policy documents, doctrine, and strategic literature. The findings indicate that operational integration has been implemented in practice, yet it has not been institutionalized as a comprehensive system, particularly in the standardization of procedures, readiness of port nodes, and continuity of cross-element coordination. Lessons from the Normandy Operation underscore the importance of integrated planning, adaptation to infrastructure constraints, and consistent command-and-control coordination. In conclusion, strengthening governance for integration, improving the readiness of key infrastructure nodes, and establishing sustainable coordination mechanisms are essential to enhance water-transport-based military mobilization in Indonesia.